Comparative biodistribution study of the new tumor tracer [123I]-2-iodo-L-phenylalanine with [123I]-2-iodo-L-tyrosine. - Kersemans, V; Cornelissen, B; Kersemans, K; Dierckx, R; De Spiegeleer, B; Mertens, J; Slegers, G (2006)
INTRODUCTION: Both A- and l-type amino acid transport are increased in tumor cells relative to normal tissue; these transport systems have been the major focus of the development of amino acid tumor tracers to overcome the limitations of [(18)F]-fluorodeoxyglucose ((18)F-FDG). The newly developed tracer 2-amino-3-(2-[(123)I]iodophenyl)propanoic acid ([(123)I]-2-iodo-l-phenylalanine) showed high and specific tumor uptake, slow renal elimination and low brain uptake. We compared [(123)I]-2-iodo-L-phenylalanine with 2-amino-3-(4-hydroxy-2-[(123)I]iodophenyl)propanoic acid ([(123)I]-2-iodo-L-tyrosine), an L-tyrosine analogue that has recently entered clinical trials. METHODS: [(123)I]-2-iodo-L-phenylalanine and [(123)I]-2-iodo-L-tyrosine were evaluated in rhabdomyosarcoma tumor-bearing athymic mice by means of dynamic planar imaging (DPI) and dissection. A displacement study with L-phenylalanine was performed to prove the specificity of tracer tumor uptake, and kinetic modeling was applied to the DPI results. Moreover, the biodistribution of both tracers was compared with that of (18)F-FDG. RESULTS: Both [(123)I]-2-iodo-L-phenylalanine and [(123)I]-2-iodo-L-tyrosine showed fast, high and specific tumor accumulation with no significant difference. However, [(123)I]-2-iodo-L-phenylalanine was cleared faster from the blood to the bladder in comparison with the tyrosine analogue. Moreover, [(123)I]-2-iodo-L-phenylalanine tumor uptake equilibrated faster with blood. Dissection showed that [(123)I]-2-iodo-L-tyrosine slightly accumulated in the liver, which was not the case for the phenylalanine analogue. In contrast to (18)F-FDG, both tracers showed low uptake in the heart and normal brain tissue, which is advantageous for tumor detection in these organs. CONCLUSIONS: [(123)I]-2-iodo-L-phenylalanine showed more promising characteristics for oncological imaging as compared with [(123)I]-2-iodo-L-tyrosine. The former tracer not only demonstrated faster blood clearance but also showed that the tracer uptake in the tumor reached its equilibrium with the blood pool activity faster, which led to faster and better tumor contrast. Moreover, both tracers could overcome an important limitation of (18)F-FDG-its high normal brain uptake.